Palladium‐Catalyzed Olefination and Arylation of Polyfluoroarenes Using Molecular Oxygen as the Sole Oxidant. Issue 16 (29th October 2015) - Huang, Qiufeng; Zhang, Xinyu; Qiu, Lin; Wu, Jiajun; Xiao, Hanbing; Zhang, Xiaofeng; Lin, Shen
Abstract: The palladium‐catalyzed cross‐dehydrogenative‐coupling of polyfluoroarenes with alkenes or simple arenes has been developed. The approach is characterized by using atmospheric pressure of molecular oxygen as the sole oxidant, and provides a straightforward and environmentally benign route to functionalized polyfluoroarenes. Abstract :